Osmotic Imbalance, Cytoplasm Acidification and Oxidative Stress Induction Support the High Toxicity of Chloride in Acidophilic Bacteria - Rivera-Araya, Javier; Pollender, Andre; Huynh, Dieu; Schlömann, Michael; Chávez, Renato; Levicán, Gloria (Frontiers in Microbiology, 2019)
In acidophilic microorganisms, anions like chloride have higher toxicity than their neutrophilic counterparts. In addition to the osmotic imbalance, chloride can also induce acidification of the cytoplasm. We predicted that intracellular acidification produces an increase in respiratory rate and generation of reactive oxygen species, and so oxidative stress can also be induced. In this study, the multifactorial effect as inducing osmotic imbalance, cytoplasm acidification and oxidative stress in the iron-oxidizing bacterium Leptospirillum ferriphilum DSM 14647 exposed to up to 150 mM NaCl was investigated. Results showed that chloride stress up-regulated genes for synthesis of potassium transporters (kdpC and kdpD), and biosynthesis of the compatible solutes (hydroxy)ectoine (ectC and ectD) and trehalose (otsB). As a consequence, the intracellular levels of both hydroxyectoine and trehalose increased significantly, suggesting a strong response to keep osmotic homeostasis. On the other hand, the intracellular pH significantly decreased from 6.7 to pH 5.5 and oxygen consumption increased significantly when the cells were exposed to NaCl stress. Furthermore, this stress condition led to a significant increase of the intracellular content of reactive oxygen species, and to a rise of the antioxidative cytochrome c peroxidase (CcP) and thioredoxin (Trx) activities. In agreement, ccp and trx genes were up-regulated under this condition, suggesting that this bacterium displayed a transcriptionally regulated response against oxidative stress induced by chloride. Altogether, these data reveal that chloride has a dramatic multifaceted effect on acidophile physiology that involves osmotic, acidic and oxidative stresses. Exploration of the adaptive mechanisms to anion stress in iron-oxidizing acidophilic microorganisms may result in new strategies that facilitate the bioleaching of ores for recovery of precious metals in presence of chloride.